Language of Instruction and Ethnic Disparities in School Success - Bakhshaei, Mahsa; Georgiou, Theophano; Mc Andrew, Marie (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2016)
In Quebec’s French-language secondary schools, youth originating from South Asia have the highest dropout rate among all immigrant-origin students, whereas in the English sector, their coethnic peers have a more positive academic profile than third-plus-generation students. Using quantitative data, this paper aims to understand the difference in school performance between these two groups. Firstly, we examine their performance through three indicators: school delay, graduation, and dropout rates. Secondly, we contrast their profile through nine characteristics. Finally, we discuss the influence of each group’s characteristics on graduation. The results reveal that the difference in performance is largely due to the characteristics of the French-sector students. The English-sector students’ success is not significantly related to having English as mother tongue or as language spoken at home.